A Closer Examination of the Temporal Relationship Between Self-Competence and Depressive Symptoms During Early Adolescence. (November 2020) - Ohannessian, Christine McCauley; Vannucci, Anna
This study examined the temporal relation between self-competence and depressive symptoms in a large, diverse, U.S. community sample of 1, 344 adolescents (51% female;X ¯ a g e = 12.73, SD = .69, range = 11-14 years). Surveys were administered to seventh- and eighth-grade students at participating high schools in the fall of 2016 and the spring of 2017. Girls reported higher levels of depressive symptoms and self-competence in behavioral conduct and close friendships than boys, whereas boys reported higher levels of self-competence in athletic, physical appearance, and social domains than girls. Results from autoregressive, cross-lagged path models indicated that depressive symptoms predicted self-competence more consistently than the reverse. There were no gender differences in the associations between self-competence and depressive symptoms. Findings from this study underscore the importance of considering both directions of effect when examining psychosocial factors associated with depressive symptoms during early adolescence.